GANGGUAN BERBAHASA PADA TOKOH ANGEL DALAM FILM â€œAYAH MENGAPA AKU BERBEDA?â€ - Verli Dwi Astuti (Universitas Sarjanawiyata Tamansiswa, 2020)
The research was conducted to look at language disorders in Angel characters in the Film â€œAyah Mengapa Aku Berbeda?â€. The conduct of this research is to see and identify the acquisition of language and forms of communication between Angel characters and the people around them. The method used in this research is descriptive qualitative then the subject in this study is the Angel figure in the Film â€œAyah Mengapa Aku Berbeda?â€ And the object is the language disorder experienced by the character. To analyze this language disorder the researcher uses Samuel A. Krik theory.